Escape from adamantane: Scaffold optimization of novel P2X7 antagonists featuring complex polycycles. Issue 4 (15th February 2017) - Barniol-Xicota, Marta; Kwak, Seung-Hwa; Lee, So-Deok; Caseley, Emily; Valverde, Elena; Jiang, Lin-Hua; Kim, Yong-Chul; Vázquez, Santiago
Graphical abstract: Abstract: The adamantane scaffold, despite being widely used in medicinal chemistry, is not devoid of problems. In recent years we have developed new polycyclic scaffolds as surrogates of the adamantane group with encouraging results in multiple targets. As an adamantane scaffold is a common structural feature in several P2X7 receptor antagonists, herein we report the synthesis and pharmacological evaluation of multiple replacement options of adamantane that maintain a good activity profile. Molecular modeling studies support the binding of the compounds to a site close to the central pore, rather than to the ATP-binding site and shed light on the structural requirements for novel P2X7 antagonists.